Evaluating Nursing Care Quality: Metrics, Models, and Practical Implications - AL-SABR, AHMED FAYEZ MOHAMMED; ASSIRI, ATHARI MOHAMMED MOUDI; AL HUMAYD, AMINAH IBRAHIM ALI; ASSIRY, MARFAYAH JABER IBRIHUM; ALOTIBI, OHOUD THAMER; ALOTIBI, ALHANOUF FARHAN; ALOTAIBI, KHULOD NAWAF; ALJUMAIAN, MARIAM MOHAMMED; ALABDULAAL, FATIMIH ABDULLAH; ALSANNAA, SAKINAH ALI; NASSER, ZAINAB MOHAMMED; ALNASSER, ZAHRA AHMAD; et al. (Journal of Posthumanism, 2024)
The concept of nursing care quality is anchored in the establishment of robust standards that guarantee patient-centered care. Quality in nursing extends beyond the administration of clinical interventions; it encompasses the holistic support of patients’ emotional, psychological, and educational needs. Nurses occupy a pivotal role as both caregivers and educators, bridging the gap between technical medical procedures and patients’ comprehension of their conditions. In times of crisis, such as pandemics, this responsibility is magnified, demanding adaptability and resilience. By maintaining patient-centered approaches under pressure, nurses foster trust, improve outcomes, and uphold the integrity of healthcare delivery.